1996
DOI: 10.1046/j.1365-2559.1996.d01-467.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of invasive growth pattern and lymphocytic infiltration in colorectal cancer

Abstract: A total of 122 specimens of colorectal cancer were re-assessed in relation to the reporting of invasive growth pattern (expanding vs. infiltrating) and presence or absence of peritumoral lymphocytic infiltrate as used in the Jass prognostic classification. Jass agreed with 69% of cases reported as infiltrating and 90% of reported as expanding. This parameter was distributed similarly amongst Dukes B and C cases in the original assessment (P = 0.27), whereas in the reviewed data infiltrating cases were more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
121
1
4

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 16 publications
(34 reference statements)
5
121
1
4
Order By: Relevance
“…For instance, it has been shown that estimating the amount of tumor-infiltrating immune cells on HE sections is sensitive to interobserver variability 5 and underestimates the true number of leukocytes in a tumor. 6 In addition, it is difficult to characterize the tumor-infiltrating immune cells morphologically, that is, whether a particular cell is a T-helper (T H , CD4 þ ), cytotoxic T lymphocyte (CTL, CD8 þ ) or natural killer (NK) cell (CD3 À /CD56 þ , and subsets of CD8 þ or CD57 þ ).…”
mentioning
confidence: 99%
“…For instance, it has been shown that estimating the amount of tumor-infiltrating immune cells on HE sections is sensitive to interobserver variability 5 and underestimates the true number of leukocytes in a tumor. 6 In addition, it is difficult to characterize the tumor-infiltrating immune cells morphologically, that is, whether a particular cell is a T-helper (T H , CD4 þ ), cytotoxic T lymphocyte (CTL, CD8 þ ) or natural killer (NK) cell (CD3 À /CD56 þ , and subsets of CD8 þ or CD57 þ ).…”
mentioning
confidence: 99%
“…Although Jass_ new grading system was shown to have superior prognostic value to Dukes staging, it has not been recommended for routine usage in standard reporting protocols because some studies have raised the criticism of poor reproducibility and reliability of the growth pattern and lymphocytic infiltrate. 20,31,32 In two previously published studies, we have shown the lack of any prognostic significance of lymphocytic infiltrate but a strong correlation between tumor growth pattern and survival in patients with LNnegative and patients with LN-positive colorectal cancer. 3,33 In the present study, we reconfirmed these data in patients classified as Stage IIA, thus demonstrating, in accordance with the experience of other authors, 2,34-37 the reliability of the growth pattern as an objective predictor of prognosis.…”
Section: Discussionmentioning
confidence: 94%
“…O padrão infiltrativo é caracterizado por glân-dulas neoplásicas separadas por pouco tecido fibroso, as quais podem ser encontradas individualmente ou em pequenos grupos infiltrando a parede intestinal e associadas a um infiltrado linfocítico. As lesões pouco dife- renciadas e as de padrão infiltrativo estão em geral associadas a um prognóstico mais reservado (7,8,13,14,15) . Alguns casos de adenocarcinoma apresentam áre-as mucoprodutoras, que correspondem ao acúmulo de mucina principalmente no meio extracelular.…”
Section: Discussionunclassified
“…Pacientes com tumores do cólon direito podem apresentar anemia devido à perda sanguínea crônica. Durante a progressão do adenocarcinoma colorretal, há invasão neoplásica através das camadas do intestino, incluindo invasão neoplásica angiolinfática, podendo levar ao surgimento de metástases hepáticas e nodais (5,6,7,8) .…”
Section: Introductionunclassified
See 1 more Smart Citation